The Centrality of Education for Indigenous Income Mobility in Canada - Haan, Michael; Chuatico, Georgina; Cornetet, Jules (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2021)
In this article, we employ a multinomial logistic regression model to determine which factors predict middle- and upper income class belonging among Indigenous and non-Indigenous people. We examine the impact of identity, education, occupation, and urbanization on income status. The positive impact of higher education is captured by the model; however, post-secondary education has a greater impact on some Indigenous groups than others. We present interaction terms between education and identity to show that investment in higher education is crucial to Indigenous people’s income attainment; however, some identity groups benefit more than others.